Estimating the Long-Run Impact of Microcredit Programs on Household Income and Net Worth - Woutersen, Tiemen; Khandker, Shahidur R. (World Bank Group, Washington, DC, 2014)
This paper investigates whether the utilization of microcredit programs has a significant impact on the income and net worth of the participants. Several micro finance institutes are optimistic on the beneficial effects of microcredit programs. Others describe microcredit with interest rates in excess of 20 percent as a poverty trap. This paper uses more than 20 years of panel data on households in Bangladesh to estimate bounds on the causal effects of microcredit programs. The analysis rejects the hypothesis that these microcredit programs are a poverty trap. Moreover, the paper finds moderately positive effects of such programs.